Sweetened kallikrein-related peptidases (KLKs): glycan trees as potential regulators of activation and activity - Guo, Shihui; Skala, Wolfgang; Magdolen, Viktor; Brandstetter, Hans; Goettig, Peter (Biological chemistry, 2014)
Most kallikrein-related peptidases (KLKs) are N-glycosylated with N-acetylglucosamine2-mannose9 units at Asn-Xaa-Ser/Thr sequons during protein synthesis and translocation into the endoplasmic reticulum. These N-glycans are modified in the Golgi machinery, where additional O-glycosylation at Ser and Thr takes place, before exocytotic release of the KLKs into the extracellular space. Sequons are present in all 15 members of the KLKs and comparative studies for KLKs from natural and recombinant sources elucidated some aspects of glycosylation. Although glycosylation of mammalian KLKs 1, 3, 4, 6, and 8 has been analyzed in great detail, e.g., by crystal structures, the respective function remains largely unclear. In some cases, altered enzymatic activity was observed for KLKs upon glycosylation. Remarkably, for KLK3/PSA, changes in the glycosylation pattern were observed in samples of benign prostatic hyperplasia and prostate cancer with respect to healthy individuals. Potential functions of KLK glycosylation in structural stabilization, protection against degradation, and activity modulation of substrate specificity can be deduced from a comparison with other glycosylated proteins and their regulation. According to the new concept of protein sectors, glycosylation distant from the active site might significantly influence the activity of proteases. Novel pharmacological approaches can exploit engineered glycans in the therapeutical context.